AN ANALYSIS ON THE USE OF CODE SWITCHING IN INSTAGRAM USED BY ENGLISH STUDENTS IN UNISMA - Marita Anjarani (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This article aims at identifying the various types of code switching and knowing the reason of using code switching in Instagram used by English students in Unisma. Code switching is a process of shifting from one language or dialect to another, depending on the social context or conversational setting. In conducting the study, the researcher used mix method research. The subjects of this study were 19 English Education Department 2017 intake students who had originally signed up as Instagram users. The data were collected through taking a screenshot and interview at the students’ Instagram post that was posted between March 18th to May 17th, 2021. The findings showed that students prefer to use Tag-switching (43,2%) and followed by inter-sentential switching (32.4%), and intra-sential switching (24,3%). The results also showed that the most common reasons are free switching, talking about a particular topic, and to emphasized point.